2011
DOI: 10.3390/ijms12074456
|View full text |Cite
|
Sign up to set email alerts
|

Silkworm Hemolymph Down-Regulates the Expression of Endoplasmic Reticulum Chaperones under Radiation-Irradiation

Abstract: We demonstrated that up-regulation of gene expression of endoplasmic reticulum (ER) chaperones (BiP, calnexin, calreticulin, ERp29) and ER membrane kinases (IRE1, PERK, ATF6) was induced by radiation in neuronal PC12 cells. However, addition of silkworm, Bombyx mori, hemolymph to irradiated cells resulted in an obvious decrease in expression of these genes, compared with a single radiation treatment. In contrast, one of the ER chaperones, “ischemia-responsive protein 94 kDa” (irp94), was up-regulated by radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The reason for this may be contention of the transcriptional factors biding to the ubiquitous enhancer occurring at the beginning of ER stress for ERp29. These results have been shown in other ERp29 experiments (7,17). Under the same experimental conditions, naloxone dose dependently increased the gene expression of ER stress sensors (ATF6, IRE1 and PERK).…”
Section: A B Csupporting
confidence: 84%
“…The reason for this may be contention of the transcriptional factors biding to the ubiquitous enhancer occurring at the beginning of ER stress for ERp29. These results have been shown in other ERp29 experiments (7,17). Under the same experimental conditions, naloxone dose dependently increased the gene expression of ER stress sensors (ATF6, IRE1 and PERK).…”
Section: A B Csupporting
confidence: 84%
“…Orthologs of malectins have been identified in D. melanogaster and A. aegypti, but have not been studied yet [27,28]. Calnexin/calreticulin chaperones have been identified in B. mori [29,30] and D. melanogaster [31,32]. In Drosophila, calnexin was reported to be related to neuron functions and sodium channel regulation [31,32].…”
Section: Insect Lectinsmentioning
confidence: 99%
“…IR has been shown to induce ER stress in rat intestinal epithelial cells, IEC-6, and neuronal PC12 cells (32,33) at a dose of 10 Gy, indicating that ER may be a cytoplasmic target of IR. However, in the current study, FTC-133 cells treated with 1, 2, and 4 Gy of radiation was not found to result in an increase in the mRNA expression of GRP78 and EDEM or XBP1 mRNA splicing.…”
mentioning
confidence: 99%